Myocardial Impact of NHE1 Regulation by Sildenafil - Escudero, Daiana S.; Pérez, Néstor G.; Díaz, Romina G. (Frontiers in Cardiovascular Medicine, 2021)
The Na+/H+ exchanger (NHE1) is a membrane glycoprotein fundamental for proper cell functioning due its multiple tasks including maintenance of intracellular pH, Na+ concentration, and volume preservation. In heart its hyperactivity has been strongly related to pathologies of different kind. In fact, NHE1 inhibition afford cardioprotection against ischemia/reperfusion injury preventing oxidative damage and apoptosis. Same strategy has shown to be effective in preventing and/or reverting hypertrophy in different animal models. By contrast, clinical trials with NHE1 inhibitors revealed lack of consistent benefits than in preclinical, and severe side effects from thromboembolic origin. Still, in certain settings primary outpoints have been achieved, disclosing that, although potentially highly effective, complete abolition of the exchanger activity may not be the best therapeutic approach. Emphasizing that NHE1 hyperactivity, represents a driving force for cardiac pathologies, a wide range of potential therapeutic targets tending to reduce such state emerged, among them, those involved in phosphorylation regulation pathways. In this group is Sildenafil, a PDE5 inhibitor drug initially promoted as a coronary vasodilator and later repurposed for erectile dysfunction, among other pathologies. Growing evidence showing Sildenafil cardioprotective effect has been achieved during later years. A distinctive characteristic of the use of Sildenafil for cardiac pathologies is that its effectiveness seems to be independent of blood pressure affecting myocardial targets directly. This mini-review focuses on the regulation of NHE1 activity by Sildenafil, and summarizes experimental results that have explored the use of Sildenafil in animal models of heart disease in which NHE1 plays an iconic role.